Human Factors Study on Light Modulation in Indirect Office Lighting - Olsen, Jo; Spaulding, Jeremy; Davey, Ernest; Ring, Charles (Proceedings of the Human Factors and Ergonomics Society Annual Meeting, 2014)
Our goal is to provide insight into the human experience of light modulation to help achieve the specific application goals of indirect office lighting. This paper explains experimental development and design, and results from a human factors experiment for an indirect office lighting application. 18 subjects experienced working for a day in a 4x4 meter office equipped with an extended cove, housing LED light modules, providing indirect lighting that varied at 2 light modulation levels and a no modulation control condition. The light modulated at a frequency of 100 Hz due to the electronic design of the rectification of the AC line voltage. The results show that subjects had little to no response for the 29% light modulation level and the 0% control. Considerable undesirable response was measured with 100% modulation. In addition we see considerable variation from subject to subject. The type of information contained in this paper is used in making decisions on design trade-offs by product development teams.